2008
DOI: 10.4103/0028-3886.43442
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne and Becker muscular dystrophies: An Indian update on genetics and rehabilitation

Abstract: The application of molecular diagnostic techniques has greatly improved the diagnosis, carrier detection, prenatal testing and genetic counseling for families with Duchenne and Becker muscular dystrophy (D/BMD) in India. The prediction of Duchenne muscular dystrophy (DMD) patients to have out-framed deletions and Becker's muscular dystrophy (BMD) patients to have in-frame deletions of dystrophin gene holds well in the vast majority of cases. Mutation detection is obviously critical for diagnosis but it may als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Multiplex PCR is the method of choice for initial screening as it is a sensitive, robust and is cost effective to assess any of the 32 exons deletions. [3,10] In contrast, to mPCR, MLPA can be used to identify duplications as well as carrier status in females. [7] Of the DMD patients, 60-75% are due to large deletions, 5-10% are due to duplications and 25-30% are due to point mutations of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex PCR is the method of choice for initial screening as it is a sensitive, robust and is cost effective to assess any of the 32 exons deletions. [3,10] In contrast, to mPCR, MLPA can be used to identify duplications as well as carrier status in females. [7] Of the DMD patients, 60-75% are due to large deletions, 5-10% are due to duplications and 25-30% are due to point mutations of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…[32] The deletion rate in our study was about 73% and was similar to the frequency reported from the other parts of India. [33] The reported frequency of dystrophin gene deletions in other countries in Asia is quite variable: 40.7% in Pakistan, [34] and 66.25% in China. [35] In Egypt, an African country, it was 61.1%.…”
Section: Carrier Testingmentioning
confidence: 98%
“…These items were numbered 2, 8, 9, 11, 12, 17, 20, 23, 24, 26, 28, 32, 33, 34 and 35. Whereas, the remaining 20 items numbered 1,3,4,5,6,7,10,13,14,15,16,18,19,21,22,25,27,29,30 and 31 reverse scored, with "one point" being "false" and "zero point" for "true" and "don"t know". The obtainable scores on the schedule ranged from 1-35.…”
Section: Measurementsmentioning
confidence: 99%
“…Parents of Indian children with DMD reported a bimodal peak in stress wherein one smaller stress peaks was observed at the time of the diagnosis and the second higher one at the time when boys become immobile. The parents in this cohort tended to use denial as a coping strategy for unusually longer periods of time and even in acceptance they experienced chronic guilt and helplessness (Nadkarni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%